Addressing cancer invasion and cell motility with quantitative light microscopy - Zicha, Daniel (Scientific reports, 2022)
The incidence of death caused by cancer has been increasing worldwide. The growth of cancer cells is not the main problem. The majority of deaths are due to invasion and metastasis, where cancer cells actively spread from primary tumors. Our inbred rat model of spontaneous metastasis revealed dynamic phenotype changes in vitro correlating with the metastatic potential in vivo and led to a discovery of a metastasis suppressor, protein 4.1B, which affects their 2D motility on flat substrates. Subsequently, others confirmed 4.1B as metastasis suppressor using knock-out mice and patient data suggesting mechanism involving apoptosis. There is evidence that 2D motility may be differentially controlled to the 3D situation. Here we show that 4.1B affects cell motility in an invasion assay similarly to the 2D system, further supporting our original hypothesis that the role of 4.1B as metastasis suppressor is primarily mediated by its effect on motility. This is encouraging for the validity of the 2D analysis, and we propose Quantitative Phase Imaging with incoherent light source for rapid and accurate testing of cancer cell motility and growth to be of interest for personalized cancer treatment as illustrated in experiments measuring responses of human adenocarcinoma cells to selected chemotherapeutic drugs.
Keywords: nádorové buněčné linie; Rats; invazivní růst nádoru; Animals; Neoplasm Invasiveness; Humans; krysa rodu Rattus; pohyb buněk; Cell Line, Tumor; Microscopy; lidé; zvířata; mikroskopie; Cell Movement